IPTEKS KETEPATAN WAKTU INFORMASI PELAPORAN KEUANGAN PADA PT. BANK BRI UNIT KAROMBASAN CABANG MANADO - Mangala, Lerry Riandy Diauw; Masuara, Harlan; Lintong, Diana (Jurnal Ipteks Akuntansi Bagi Masyarakat, 2018)
In the company's timeliness is the main thing especially the timeliness when entering the office inÂ  the morning. timeliness in work is very influential on the quality of employees, on time a company can assess the quality of existing employees. from a research employee who arrived late will be deducted from the salary. so that in the future there will be less laziness in each employee, the company must provide more sanctions. in a way that employees will feel motivated to come to the office early. And for the future the quality of employees will rise.Keywords :Timeliness,Â  Quality employees